MUSCULOSKELETAL ULTRASONOGRAPHIC VALUES FOR DIFFERENT SEVERITIES OF CARPAL TUNNEL SYNDROME IN A PAKISTANI COHORT - Akhtar, Noreen; Ayaz, Saeed Bin; Khan, Atif Ahmed; Yasmeen, Rehana (Pakistan Armed Forces Medical Journal, 2020)
Objective: To identify the cutoff values suggested by musculoskeletal ultrasound for the diagnosis of different severities of carpal tunnel syndrome and compare the parameters among males and females and patients with and without comorbidities of hypertension, diabetes mellitus, and hypothyroidism. Study Design: A cross-sectional study. Place and Duration of Study: Department of Electrodiagnosis, Armed Forces Institute of Rehabilitation Medicine Rawalpindi, from Mar to Jun 2017. Methodology: Adults (20-75 years) with clinical and electrodiagnostic diagnosis of carpal tunnel syndrome were grouped into having mild, moderate, and severe disease and examined through musculoskeletal ultrasound for cross-sectional area and flattening ratio. A cross-sectional area of >9.8 mm2 was considered diagnostic of carpal tunnel syndrome. Results: There were 11 (22.9%) males and 37 (77.1%) females (mean age: 47 ± 9 years). Based on electrodiagnostic studies, 4 (8.3%) patients had mild, 18 (37.5%) had moderate, and 26 (54.2%) had severe carpal tunnel syndrome. All patients had carpal tunnel syndrome based on the cutoff value of musculoskeletal ultrasound. There was no significant difference among mean values of cross-sectional area and flattening ratio for both genders and for individuals who had diabetes mellitus, hypertension, or hypothyroidism compared to those who did not have these diseases. The cross-sectional area cutoff value for mild carpal tunnel syndrome was ≤14.4 mm2, for moderate carpal tunnel syndrome was 14.4 -15.55 mm2 and for severe carpal tunnel syndrome was >15.55 mm2. Conclusion: Musculoskeletal ultrasound is a useful modality to determine severity of carpal tunnel syndrome with cross-sectional area values of ≤14.4 mm2, 14.4-15.55 mm2, and >15.55 mm2 corresponding to mild, moderate, and severe carpal tunnel syndrome.